Instrumentos de responsabilidade socioambiental nas atividades de exploração e produção de petróleo e gás natural aplicados às comunidades e povos tradicionais na margem equatorial maranhense - SILVA , Ludmilla Valente Viana (2024)
The debate surrounding socioenvironmental instruments in oil and gas exploration and production (E&P) activities in Brazil takes on a sense of urgency when contextualized within the potential impacts associated with communities and traditional peoples situated on the Brazilian Equatorial Margin, specifically in the state of Maranhão. For this reason, this dissertation aims to analyze and propose the improvement, from a countercolonial perspective of sustainable development, of socioenvironmental responsibility instruments applicable to the preservation of the ways of life of communities and traditional peoples located on the Maranhão Equatorial Margin who may be affected by potential E&P of oil and gas in the region. The implementation of an E&P project, especially in a new exploration frontier region such as the Brazilian Equatorial Margin, is characterized by a complex and challenging initiative due to its association with a space of rich biodiversity inhabited by communities and traditional peoples who, due to their bio-interaction, are more vulnerable to environmental erosion. The process of colonization and mental monoculture, marked by racial dehumanization in favor of profit, coupled with developmentalism and the erosion of natural resources, has created an environment of environmental racism that further compromises the resistance process of Brazilian communities and traditional peoples. The current scenario of socioenvironmental responsibility in oil and gas E&P is undergoing a period of change due to the diversification of the energy matrix towards a low-carbon economy in response to the climate emergency. Government agencies such as the National Agency of Petroleum, Natural Gas and Biofuels (ANP) are in a phase of adaptation to new energies, dynamics, and socioenvironmental demands that have resulted in the diversification of the Brazilian regulatory framework. Socioenvironmental responsibility instruments currently in force in the energy sector, such as the Strategic Environmental Assessment (SEA), require adaptation of their models as well as the implementation of new instruments such as the Social License to Operate (SLO), which are in line with the Paris Agreement, will be necessary for Brazil to fulfill the commitments assumed in the Paris Agreement. It is also identified that the improvement of socioenvironmental instruments provided for in E&P Contracts and the celebration of Technical Cooperation Agreements constitute intermediate measures for producing effects in this area, favoring the process of adaptation to the scenario of climate crisis. The methodology applied for the development of this dissertation uses a combination of bibliographic research and documentary analysis in a countercolonial approach to sustainable development. The procedures used were: 1. Bibliographic Research that analyzed repositories involving: traditional knowledge, oil and gas exploration and production, environmental justice and racism, ways of life of communities and traditional peoples, biodiversity and Geography of the state of Maranhão, Brazilian Equatorial Margin, sustainable development and socioenvironmental responsibility. 2. Documentary Analysis that analyzed Brazilian regulations associated with the exploration and production of oil and gas, including socioenvironmental responsibility instruments provided for in the legislation. This dissertation is a product of the Graduate Program in Culture and Society, Research Line 2 - Culture, Education and Technology, an interdisciplinary master's degree offered by the Federal University of Maranhão. In addition, the author is a collaborating researcher of the following Research Groups: i. Observatório Cultural do Maranhão; ii. Laboratory of Science and Environmental Planning; iii. Research Group on Law, Nature and Society; and iv. Research Group Epistemology of Anthropology, Ethnology and Politics.